PENGARUH PENGAWASAN DAN LOYALITAS TERHADAP KINERJA KARYAWAN INDUSTRI TV KABEL (Studi Pada PT.Zi Vision Cabang Pangkalan Kerinci Kabupaten Pelalawan) - Astuti, Yuli; Heriyanto, Meizy (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This study aims to determine how the influence of supervision (standard definition, Monitoring, Measurement of work, Comparing and corrective actions / correction)and loyalty (Obey the rules, responsibilities and work attitude) on employee performance (factor capacity and factor of motivation) industrial cable tv on PT.Zi Vision Branch Pangkalan Kerinci Pelalawan. The population in this study is karyaan on PT.Zi Vision Branch Pangkalan Kerinci sampling Pelalawan with 50 drawn using census method. measurement techniques using Likert scale and the types and sources of data in the form of primary and secondary data while the data collection techniques with a questionnaire and interviews as research instruments. As well as using multiple linear regression data analysis, determination, t test and f test with SPSS.From the research data that includes test validity, The reliability, and multiple linear regression, the results showed no significant relationship between supervision terhaap employee performance with the calculated of t test is known that t (6,213) > t tabel (2,012) dan Sig.(0,000) < 0,05 it can be concluded that the variable control significantly influence employee performance in PT.Zi Vision Branch Pangkalan Kerinci Pelalawan and of the t test results are known t arithmetic (3,184) > t tabel (2,012) dan Sig.(0,003) < 0,05 it can be concluded that the loyalty variable significant effect on the performance of employees at PT. Zi Vision Branch Pangkalan Kerinci Pelalawan.And there is significant influence between supervision and loyalty to employee performance with the calculated Unknown R squre is the coefficient of determination. And obtained a value of R squre at 0.616. What this means is that the variable control donations influence and loyalty to the employee performance was 61.6%. While the remaining 38.4% is influenced by other variables such as the provision of training and education that are not included in the regression analysisKeywords: Monitoring, Loyalty and Employee Performance